PENGARUH PENERBITAN SURAT TEGURAN, SURAT PAKSA, DAN SURAT PERINTAH MELAKUKAN PENYITAAN TERHADAP PENCAIRAN TUNGGAKAN PAJAK OLEH WAJIB PAJAK BADAN (Studi Empiris di Kantor Pelayanan Pajak Madya Pekanbaru) - Dhyta Maya Angraeny; Vince Ratnawati; Lila Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study is aimed to examine and analyze Influence Of Publishing The Reprimand Letter, The Forced Letter and The Warrant Foreclosing To Disbursement of Tax Arrears By Corporate Taxpayers. The population in this study is corporate taxpayer which has been registered on KPP Madya Pekanbaru. The sample was determined by the purposive sampling method, where corporate taxpayer that hold theReprimand Letter, The Forced Letter and The Warrant Foreclosing which had been issued by Kantor Pelayanan Pajak Madya Pekanbaru from year 2011 until 2015 (5 years). Data analysis conducted with multiple linear regression model by using software SPSS version 22,0. The independent variable in this study is the reprimand letter which measured using total number of reprimand letter, forced letter and warrant foreclosing which has issued, besides, the dependent variable is Disbursement of Tax Arrears measured by total number of outstanding tax which based on STP, SKP, SKpKB and SKPKBT.As the result of the test that has been done using the partial regression test (t test) showed that the independent variables, the reprimand letter and the forced letter, has a significant effect on disbursement of tax arrears. Meanwhile the warrant foreclosing has no effect on disbursement of tax arrears. Based on total adjusted R-square result proved that variables of Publishing The Reprimand Letter, The Forced Letter and The Warrant Foreclosing To Disbursement of Tax Arrears By Corporate Taxpayersresults of 22,9% while the rest of 77,1% were affected by other variables that were not performed in this studyKeywords :Disbursement of Tax Arrears, The Reprimand Letter, The Forced Letter and The Warrant Foreclosing